2014
DOI: 10.1007/s10549-014-3191-4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic diversity of tamoxifen metabolites and estrogen receptor genes in Hispanics and non-Hispanic whites with breast cancer

Abstract: Ethnic differences in patient genetics and breast cancer (BC) biology contribute to ethnic disparities in cancer presentation and patient outcome. We prospectively evaluated SNPs within phase I and phase II tamoxifen (TAM) metabolizing enzymes, and the estrogen receptor gene (ESR1), aiming to identify potential pharmacogenomic ethnicity patterns in an ER-positive BC cohort constituted of Hispanic and Non-Hispanic White (NHW) women in South Texas. Plasma concentrations of TAM/metabolites were measured using HPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
2
3
0
Order By: Relevance
“…The concentration range for each compound observed here agrees with previous reports (Dezentjé et al, ; Hertz et al, ; Lee et al, ; Lorizio et al, ; Rangel et al, ). In addition, sample reconstitution in the least possible amount of diluent allowed quantification of tamoxifen and its metabolites within the linear intervals in plasma samples (see below).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The concentration range for each compound observed here agrees with previous reports (Dezentjé et al, ; Hertz et al, ; Lee et al, ; Lorizio et al, ; Rangel et al, ). In addition, sample reconstitution in the least possible amount of diluent allowed quantification of tamoxifen and its metabolites within the linear intervals in plasma samples (see below).…”
Section: Resultssupporting
confidence: 92%
“…1, Internal standard (100 ng/mL); 2, E-endoxifen (20 ng/mL); 3, Z-endoxifen (20 ng/mL); 4, 4-hydroxytamoxyfen (20 ng/mL); 5, Z-tamoxifen (250 ng/mL) FIGURE 2 Representative chromatogram of the lowest concentration from the standard curve. 1, E-Endoxifen (3 ng/mL); 2, Z-endoxifen (3 ng/ mL); 3, 4-hydroxytamoxyfen (3 ng/mL); 4, Z-tamoxifen (50 ng/mL) The concentration range for each compound observed here agrees with previous reports (Dezentjé et al, 2015;Hertz et al, 2015;Lee et al, 2003;Lorizio et al, 2012;Rangel et al, 2014). In addition, sample reconstitution in the least possible amount of diluent allowed quantification of tamoxifen and its metabolites within the linear intervals in plasma samples (see below).…”
Section: Figuresupporting
confidence: 91%
See 1 more Smart Citation
“…This is not the case with all pharmacogenetic associations, as evidenced by the inferior performance of genetically guided warfarin dosing strategies in AfricanAmerican patients [32], which has been attributed to racial differences in the effect of clinical and genetic factors [33]. Interestingly, greater endoxifen concentrations have been reported for Hispanic patients in comparison with nonHispanic white patients [34]. This could be partially attributable to the lower frequency of CYP2D6 low-activity alleles found in the Hispanic cohort; however, within the CYP2D6 EM group, Hispanic patients had greater endoxifen concentrations.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Recently, the genetic evidence explaining incidence and survival disparity were explored, implying a biological difference between whites and blacks. 33 – 36 Our data demonstrated that black breast cancer patients displayed more advanced tumors at the time of diagnosis. Furthermore, race-specific survival disparity can be partially attributed to the different SES distribution between them, specifically a bigger proportion of whites belong to low-poverty group.…”
Section: Discussionmentioning
confidence: 68%